Oral Presentations Abstracts: INFORMED CONSENT FOR ORGAN TRANSPLANTATION IN OLDER ADULTS: ARE PATIENT DECISION AIDS THE SOLUTION FOR SUCCESSFUL IMPLEMENTATION OF SHARED DECISION-MAKING IN TRANSPLANT CLINICAL PRACTICE? - GROSSI, Alessandra Agnese; NICOLI, Federico; TESTA, Jacopo; PICOZZI, Mario (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Informed consent (IC) in older adults (≥ 70 years of age) is often complex. This holds even truer in the setting of organ transplantation (OTx), requiring patients to be informed of the risks and benefits associated with multiple options: whether or not to pursue a transplant, to opt for a living – where appropriate – or deceased donor, to consider a variety of choices concerning the potential for poorer organ quality or increased risk of disease transmission and others. IC overlaps with shared decision-making (SDM) in the presence of high-risk procedures, with low levels of certainty, and when two or more treatment alternatives exist. Patient decision aids (PDAs) (i.e. paper-based/electronic evidence-based tools) have been developed to complement and enhance SDM in clinical practice. Studies have proven PDAs to be an effective means to improve transplant knowledge, to foster patient participation, and to diminish decisional conflict across different settings in OTx. However, research is lacking on the effectiveness and appropriateness of these tools in older adults, which are increasingly entitled to receive OTx. The objective of our work is 1) to present the challenges posed by the use of PDAs in this group of patients and 2) to identify gaps so as to inform the agenda for research on this emergent issue. Our findings suggest that future studies should aim to the development, implementation and evaluation of PDAs for the oldest, more vulnerable segments of this specific patient population.